Representasi Kearifan Ekologi Budaya dalam Film Melody Kota Rusa (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Cultural maintenance in Indonesia aims to preserve the cultural diversity of the Indonesian people, including traditions, arts, languages, customs, and cultural values. Culture plays a role in the formation of groups about the traditions of life inherited in society. One of the film's works reflecting people's lives was Melody Kota Rusa. Against the backdrop of Papuan culture, the film features traditions, customs, beliefs, and values still held in high esteem by the indigenous Papuan people. The existence of the movie Melody Kota Rusa can be an information medium about cultural ecology wisdom. The film can also be understood as a tool to convey messages and information to students. That the culture in Indonesia is so numerous and vast that it's assembled through the medium of storytelling. This study focused on the cultural ecology contained in the movie Melody Kota Rusa. The analysis in this study aims to explore the forms of cultural ecology that appear in the film Melody Kota Rusa, using semiotics studies to identify the cultural ecological symbols contained in the film, by applying Julian H. Rusa's theory of cultural ecology. Steward. This study uses a qualitative method, in which research is conducted with descriptive properties through analytical methods to collect data, sampling or data sources in this study by watching Melody Kota Rusa films carefully all scenes, dialogs, music, visual images, and other subjects. The film's setting is related to Papuan culture. Data collection techniques with triangulation and data analysis are qualitative.